All Days 2004
DOI: 10.2118/89362-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Micro-Model Study: The Mechanism of Water Alternative Gas Displacement in Porous Media

Abstract: Water-alternating gas (WAG) displacement is a pronounced technique to improve gas or/and water injection in heterogeneous reservoirs. For the last half century it has been successfully applied to more than 60 oilfields worldwide. However, its mechanism still deserves further investigation. In this work, a series of water, gas, and WAG displacement studies were conducted with a sets of glass micro-models which were reproduced from a target reservoir rock by copying the pore structure images in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Although the saturation of the gas phase may not be affected significantly, this causes disconnection of continuous gas clusters, reducing the gas phase relative permeability. It has been observed that continued cycles of gas/water injection lead to progressively lower gas relative permeability and additional oil recovery in both micromodel and core experiments (Egermann et al, 2000;Sohrabi et al, 2000;Element et al, 2003;Feng et al, 2004van Dijke et al, 2004. However, most reservoirs are mixed-or oil-wet where gas is not necessarily the most non-wetting phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although the saturation of the gas phase may not be affected significantly, this causes disconnection of continuous gas clusters, reducing the gas phase relative permeability. It has been observed that continued cycles of gas/water injection lead to progressively lower gas relative permeability and additional oil recovery in both micromodel and core experiments (Egermann et al, 2000;Sohrabi et al, 2000;Element et al, 2003;Feng et al, 2004van Dijke et al, 2004. However, most reservoirs are mixed-or oil-wet where gas is not necessarily the most non-wetting phase.…”
Section: Introductionmentioning
confidence: 99%
“…A major benefit of employing such a transparent porous model is the possibility of studying how the geometry of the porous network, pore space topology, and connectivity would affect fluid flow patterns, and studying the trapping of fluids within the network of pores. Various pore patterns including geometric patterns (both homogeneous and heterogeneous) as well as rock‐look‐alike patterns can be designed and etched …”
Section: Methodsmentioning
confidence: 99%
“…During the steam injection process in the bitumen reservoir, the porous structure of the reservoir rock significantly influences the recovery rate [19][20][21][22][23][24]. The existence of three-phase flow (i.e., steam, water and bitumen) additionally complicates the displacement process.…”
Section: Introductionmentioning
confidence: 99%